PENGARUH PROMOSI BERBASIS MEDIA SOSIAL TERHADAP PEMASARAN HASIL PANEN KELOMPOK WANITA TANI ROAY LESTARI KOTA TASIKMALAYA - Mahmudah, Salma; Aulia Azqa, Raisa; Aulia Putri, Mila; Zahra, Ardiyanti; Kedjora Silvanissa, Lintang; Sri Astuti, Yani (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
Currently, social media not only function as a communication tool but has developed into a promotional and marketing tool. This study aims to determine the strategy, effectiveness, and factors that influence the success of the promotion of the Roay Lestari Women's Farmers Group through social media. The research methodology used is descriptive qualitative which produces written or spoken words from people and observed behavior. The results show that the promotional strategy carried out by KWT Roay Lestari focuses on building personal branding. In its effectiveness, members of KWT Roay Lestari stated that social media has become an effective promotional tool in product marketing with a contribution of around 80%. The success of promotion at KWT Roay Lestari is influenced by content factors and communication with consumers. A comparison of the results of online marketing using social media and offline marketing shows that online marketing is more influential and has long-term potential since KWT Roay Lestari was founded until now. Offline marketing depends on the type of product and commodity in demand.